Microstructural characterization of dental zinc phosphate cements using combined small angle neutron scattering and microfocus X-ray computed tomography - Viani, Alberto; Sotiriadis, Konstantinos; Kumpová, Ivana; Mancini, Lucia; Appavou, Marie-Sousai (Dental materials, 2017)
OBJECTIVE: To characterize the microstructure of two zinc phosphate cement formulations in order to investigate the role of liquid/solid ratio and composition of powder component, on the developed porosity and, consequently, on compressive strength. METHODS: X-ray powder diffraction with the Rietveld method was used to study the phase composition of zinc oxide powder and cements. Powder component and cement microstructure were investigated with scanning electron microscopy. Small angle neutron scattering (SANS) and microfocus X-ray computed tomography (XmCT) were together employed to characterize porosity and microstructure of dental cements. Compressive strength tests were performed to evaluate their mechanical performance. RESULTS: The beneficial effects obtained by the addition of Al, Mg and B to modulate powder reactivity were mitigated by the crystallization of a Zn aluminate phase not involved in the cement setting reaction. Both cements showed spherical pores with a bimodal distribution at the micro/nano-scale. Pores, containing a low density gel-like phase, developed through segregation of liquid during setting. Increasing liquid/solid ratio from 0.378 to 0.571, increased both SANS and XmCT-derived specific surface area (by 56% and 22%, respectively), porosity (XmCT-derived porosity increased from 3.8% to 5.2%), the relative fraction of large pores ≥50μm, decreased compressive strength from 50±3MPa to 39±3MPa, and favored microstructural and compositional inhomogeneities. SIGNIFICANCE: Explain aspects of powder design affecting the setting reaction and, in turn, cement performance, to help in optimizing cement formulation. The mechanism behind development of porosity and specific surface area explains mechanical performance, and processes such as erosion and fluoride release/uptake.
Keywords: Zinc Phosphate Cement; pevnost v tlaku; Small angle neutron scattering; Scattering, Small Angle; Zinc phosphate cements; Acid-base cements; Microscopy, Electron, Scanning; Tomography, X-Ray Computed; fosforečnany vápenaté; Calcium Phosphates; mikroskopie elektronová rastrovací; Bone Cements; maloúhlový rozptyl; zubní cementy; kostní cementy; X-ray micro-computed tomography; Materials Testing; X-Ray Diffraction; zinkfosfátový cement; Compressive Strength; difrakce rentgenového záření; Zinc oxide; testování materiálů; X-ray powder diffraction; Dental Cements; počítačová rentgenová tomografie